The Improvement of Health Service Effectiveness and Efficiency Through the Implementation of Information Technology at PKU Muhammadiyah Mayong Jepara Hospital - Iqbal, Muhammad; Paramarta, Vip; Kosasih, Kosasih (PSPP JOURNALS, 2024)
This study aims to analyze the impact of information technology implementation on the effectiveness and efficiency of services at PKU Muhammadiyah Mayong Jepara Hospital. The application of information technology is expected to improve service quality by facilitating quick, accurate, and easy access to medical information. In this study, a descriptive quantitative approach was used to measure the effectiveness and efficiency of hospital services, involving 100 respondents selected using purposive sampling method. Data was collected through observation and questionnaires, and analyzed using multiple linear regression method with the help of SPSS software version 25. The results showed that the application of information technology has a significant influence on the effectiveness and efficiency of hospital services. Effectiveness is measured based on patient satisfaction, appropriate clinical decision-making, and prevention of medical errors. While efficiency is measured through indicators of BOR (Bed Occupancy Rate), ALOS (Average Length of Stay), TOI (Turn Over Interval), and BTO (Bed Turn Over). The implementation of information systems is proven to be able to improve productivity, reliability, and speed of hospital services. This research provides a theoretical contribution in understanding the role of information technology in the health sector, as well as providing practical benefits for hospital management in improving service strategies that are more efficient and effective.